It is just a generalization to the above answers
(x+a)(x+b) = x^2 + (a+b)x +ab
co-efficient of x is (a+b).
Here, a = -2, b = 10 hence co-efficient of x is -2+10 = 8
2006-09-09 16:28:36
·
answer #1
·
answered by dipid 2
·
0⤊
0⤋
8
(x-2) (x+10)= x^2 + 10x -2x -20 = x^2 + 8x -20
hence co-efficient of x = 8
2006-09-09 20:03:09
·
answer #2
·
answered by dipak s 1
·
0⤊
0⤋
8
2006-09-09 16:39:36
·
answer #3
·
answered by reha s 1
·
0⤊
0⤋
The coefficient of x in (x-2)(x+10) is +8
(x-2)(x+10)= x^2 +10x -2x -20 =x^2 + 8x -20
Hence, coefficeint of x is +8
2006-09-09 20:04:39
·
answer #4
·
answered by Jay D 1
·
0⤊
0⤋
In general
(x+a)(x+b) = X^2 +(a+b)x + a*b
In this case :
a= -2
b+ 10
coefficient of x is : (a+b)
= -2 + 10
= 8
2006-09-09 17:08:02
·
answer #5
·
answered by sunny 2
·
0⤊
0⤋
Use the distributive property:
(x-2) (x+10)=
x^2-2x+10x-20=
x^2+8x-20.
The coefficient of the x term is therefore 8.
2006-09-09 16:08:12
·
answer #6
·
answered by just♪wondering 7
·
0⤊
0⤋
(x - 2)(x + 10) = x^2 + 8x - 20. Using the FOIL method, first you multiply the first terms (x)(x) = x^2. Multiplying the outside terms (x)(10) = 10x. Next, multiply the inside terms (-2)(x) = -2x. Finally, multiply the last terms (-2)(10) = -20. Combining terms yields x^2 + 8x - 20.
2006-09-09 17:34:13
·
answer #7
·
answered by CSUFGrad2006 5
·
0⤊
0⤋
The coefficient of x is 8 in this problem.
because... x^2+10x-2x-20 then x^2+8x-20
2006-09-09 16:06:52
·
answer #8
·
answered by J B 1
·
0⤊
0⤋
You would distribute the first set of parenthisies throuhg the second i.e you would have x*x, x*10, x*-2, -2*10 for x^2+8x-20
so the coeffcient is 8.
2006-09-09 16:45:22
·
answer #9
·
answered by Sniper 4
·
0⤊
0⤋
ans 8
for coeff of x we are supposed to multiply x with 10 n x with -2
so we get 10x and -2x add this to get 8x
2006-09-12 18:16:07
·
answer #10
·
answered by hanspie 2
·
0⤊
0⤋